Rehearsing a Revolution: Boal’s Forum Theater as a “4 trans+” Approach to Bi/Multilingual Teacher Preparation and Development - Morales, Amanda R.; Catalano, Theresa; Bock Thiessen, Crystal (International Journal of Multicultural Education, 2025)
In this paper, we, university instructors, explore the possibilities of Forum Theater and its potential significance for preparing future/practicing teachers to work with bi/multilingual populations. Inspired by a 4-trans+ approach, we use arts and community-based (ACB) pedagogies influenced by Arts Practice Research. Our analysis reveals the power of a 4-trans lens with the addition of transmediation to mitigate teacher learners’ fear and anxiety in working across difference, breaking down stereotypes, developing interculturality (including critical consciousness), and facilitating a sense of belonging and agency among participants.